Network analysis based on TCGA reveals hub genes in colon cancer - Wu, Fenzan; Yuan, Guoping; Chen, Junjie; Wang, Chengzu (Contemporary Oncology/Współczesna Onkologia, 2017)
Colorectal cancer (CRC) is the third most widespread cancer in the world. Although many advances have been made in molecular biology, novel approaches are still required to reveal molecular mechanisms for the diagnosis and therapy of colon cancer. In this study, we aimed to determine and analyse the hub genes of CRC. First, we explored the mRNA and microRNA (miRNA) expression profiles of colon carcinoma, then we screened target genes of differentially expressed miRNAs and obtained the intersection between differently expressed genes and target genes. Gene Ontology (GO) classification and KEGG pathway analysis of differently expressed genes were performed, and gene-miRNA and TF-gene-miRNA networks were constructed to identify hub genes, miRNAs, and TFs. In total, 3436 significant differentially expressed genes (1709 upregulated and 1727 downregulated) and 216 differentially expressed miRNAs (99 upregulated and 117 downregulated) were identified in colon cancer. These differentially expressed genes were significantly enriched in GO terms and KEGG pathways, such as cell proliferation, cell adhesion, and cytokine-cytokine receptor interaction signalling pathways. GCNT4, EDN2, and so on were located in the central hub of the co-expression network. MYC, WT1, mir-34a, and LEF1 were located in the central hub of the network of TF-gene-miRNA. These findings increase our understanding of the molecular mechanisms of colon cancer and will aid in identifying potential targets for diagnostic and therapeutic usage.